Penerapan Model Problem Based Learning Berbantuan DeFT E-Worksheet untuk Meningkatkan Kemampuan Pemecahan Masalah pada Materi Fluida Statis - Tantri Rahmayu; Muhamad Gina Nugraha; Muslim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The topic of static fluids requires students to understand concepts in the context of everyday phenomena. However, problem-solving skills in this subject remain a challenge because students tend to apply formulas directly without fully understanding the context of the problem. This situation highlights the need for active, context-based problem-solving learning and the support of targeted representations. Therefore, this study aims to analyze the application of the Problem-Based Learning (PBL) model, supported by Design, Function, and Task (DeFT) e-worksheets, in improving students’ problem-solving skills in static fluid mechanics. This study employed a pre-experimental design with a one-group pretest-posttest format. The research sample consisted of 33 11th-grade science students at a MAN in Bandung Regency, selected using convenience sampling. Research instruments included an observation sheet for instructional implementation, a problem-solving skills test, and a student response questionnaire. Data were analyzed using implementation percentages, N-Gain, the Wilcoxon test, Cohen’s d effect size, and descriptive percentage analysis. The results showed that the implementation of the PBL syntax achieved an average of 86.72%, falling into the “very good” category. Problem-solving skills improved, with an N-Gain of 0.39 in the “moderate” category. The Wilcoxon test showed that posttest scores were significantly higher than pretest scores (Z = -4.978; p < 0.001), with an effect size of 2.259 in the large category. Student responses fell into the “good” category across all ARCS dimensions. Thus, the implementation of the PBL model supplemented by DeFT e-worksheets demonstrated effectiveness in improving the problem-solving skills of the students in the study group, as evidenced by the increase in N-Gain, the results of the hypothesis testing, and the effect size. Future researchers are recommended to involve a control group and apply the model to broader samples or different physics topics to obtain stronger evidence regarding its effectiveness.